1971
DOI: 10.1172/jci106614
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in thyroid hormone economy in patients with hydatidiform mole

Abstract: A B S T R A C T Studies of several aspects of thyroid hormone economy have been conducted in 11 patients before and after removal of a molar pregnancy. Before evacuation of the mole, all patients demonstrated moderately to greatly elevated values for thyroidal 'I uptake, absolute iodine uptake, and serum protein-bound-I. Values for serum PBI and serum thyroxine (T4) concentration were consistently and often greatly increased, averaging more than twice those found in normal pregnancy and three times those in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It is also of clinical interest that hyperthyroidism is present in cases of trophoblastic neoplasia (Odell et al, 1963;Kock et al, 1966;Galton et al, 1971;Hershman et al, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…It is also of clinical interest that hyperthyroidism is present in cases of trophoblastic neoplasia (Odell et al, 1963;Kock et al, 1966;Galton et al, 1971;Hershman et al, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…The authors speculated that an excessive amount of the extracted molar stimulator was responsible for the hyperthyroidism in both patients that resolved following surgical extirpation of the moles. Galton et al [ 54 ] reported the same year thyroid tests done in 11 patients, before and following the extraction of a molar pregnancy. They confirmed previous studies by Dowling et al [ 55 ] that called attention of the striking abnormalities in several aspects of thyroid hormone economy in three patients with molar pregnancy.…”
Section: Etiologymentioning
confidence: 99%
“…Normal TSH responsiveness was an expected phenomenon during pregnancy as, in that condition, free triiodothyronine (T3) and thyroxine (T4) levels remained identical to that of healthy non pregnant women (Malkasian 8c Mayberry 1970;Galton et al 1975). …”
Section: Tsh Responsivenessmentioning
confidence: 99%